Voluntary Assets and Income Declaration Scheme a Panacea to Tax Evasion in Edo State, Nigeria - Paul Atagamen Aidonojie (Fakultas Hukum Universitas Lampung, 2023)
In Edo State, taxation is a primary revenue-generating tool often used to finance most public projects. It is apt to state that most individuals residing in Edo State are into small, medium, and large-scale businesses. However, business owners in Edo State often evade and avoid tax payments for the following reasons; taxes leveled on citizens or companies are numerous, excessive tax rates, and others. Given this, several taxpayers in Edo State have not been able to remit tax due for several years and without the hope of remitting the same. It is concerning that this study tends to adopt a hybrid research methodology in exploring the process of localizing the Voluntary Assets and Income Declaration Scheme (VAIDS) policy. In order to curb tax evasion and avoidance and generate more revenue in Edo State. The study, therefore, found that there is a high level of tax evasion and avoidance and that localizing the VAIDS policy will help curtail incidences of tax evasion and avoidance. It was, therefore, recommended and concluded that localizing the voluntary asset and income declaration scheme in Edo State will be an appropriate tax tool for curbing tax evasion and avoidance and improving internally generated revenue.